THE ROLE OF COMMUNITY-BASEDCHILDREN PROTECTION ACTIVIST (PATBM) IN THE CHILD PROTECTION - Ms dianawati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
AbstractThis study based on the number of cases of child abuse, the exploitation of children to be employed as a seller of "coet" and marriage on the child's age. Jayamekar village elected as research area because Jayamekar village has an extremely high level of exploitation of children because there is one area in the village which became the center of Coet (mortar) manufacture which marketed in the city - the city of West Java and outside West Java. This research uses qualitative approach and research method applied case study. The purpose of this research is the activities of the activist include strengthening norms, improving parent skills related to parenting, improving the skills of children related to rejecting the violence, and responding to child protection cases. The role of the Activist as an agent of innovation includes the role of education, the role of dissemination of innovation, the role of facilitation, the role of consultation, the role of advocacy, the role of supervision and evaluation monitoring consists of activities: a. Melting away with target communities b. Mobilize the community by making changes c. Strengthening relations with target communities.This research uses role theory, community-based education, and community empowerment. This research resulted in the role of PATBM activists who able to improve the quality of life, empowerment, and hatching of child protection issues in Jayamekar Village, Padalarang, West Bandung.Keywords: the role, activists, child protection